Analisis Strategi Pemasaran Di Era New Normal Pada Biro Perjalanan Wisata Di PT. Bintang Jelajah Wisata Bukittinggi - Friyani, Widya; Henmaidi, Henmaidi (CV. ITTC INDONESIA, 2022)
This study aims to determine the marketing strategy in the new normal era at the travel agency at PT. Bintang Jelajah Wisata Bukittinggi through a SWOT analysis. This research is a field research with qualitative research type, the method used in this research is SWOT analysis. Based on the results of the SWOT matrix for alternative S-O strategies that can be used by the company, namely increasing company development, increasing good bonding relationships with customers, increasing company revenues, utilizing technology to provide services to customers, and developing travel services throughout Indonesia. The alternative W-O strategies that can be used by companies include five alternative strategies, namely maximizing marketing through print media, increasing cooperative income, utilizing technology to provide services to customers, developing businesses that are not only focused on West Sumatra, and making staffing SOPs. Furthermore, the alternative S-T strategy that can be used by the company includes five alternative strategies, namely developing tour packages to various regions, making regulations and SOPs for the use of facilities for customers, updating office facilities such as computers and laptops, increasing promotions that are more intensive in all media to increase customer satisfaction. market share, and improve company performance by utilizing information and communication technology. For other research, it is recommended to combine other methods in analyzing marketing besides using the SWOT analysis method.